Base-line susceptibility of field populations of Rhyzopertha dominica (F.) to spinosad in Australia. (January 2017) - Nayak, Manoj K.; Daglish, Gregory J.
Abstract: Spinosad has recently been registered in several countries for long-term protection against a range of stored grain insects including the lesser grain borer, Rhyzopertha dominica (F.). The potential for development of resistance to spinosad is demonstrated by the existence of resistance in many insect pests of agriculture. The aim of this study was to determine the base-line susceptibility of R. dominica to spinosad, to provide a basis for future resistance monitoring. Eighteen insect populations of R. dominica were collected from field storage sites across four States within Australia, and exposed to a range of spinosad rates, including its current registered rate of 1 mg kg −1 (1 ppm). Base-line susceptibility was assessed based on adult mortality and production of F1 adults. Comparison of LC50 and LC99.9 indicated the existence of low level of variation among the tested R. dominica populations, in their susceptibility to spinosad. For adults, there was a narrow range of LC50 values with the highest (0.027 ppm) being 2.5 × the lowest (0.011 mg kg −1 ). Similarly, LC99.9 values showed a narrow range with the highest (0.36 mg kg −1 ) being 3.6 × the lowest (0.10 mg kg −1 ). For adult progeny produced in spinosad treated grain, there was a narrow range of LC50 values with the highest (0.025 mg kg −1 ) being 5 × the lowest (0.004 mg kg −1 ) and the highest LC99.9 values (0.67 mg kg −1 ) being 5 × the lowest LC99.9 (0.13 mg kg −1 ). Based on the data generated from this study, we recommend a dose of 1 mg kg −1 (1 ppm) to be used to discriminate between susceptible and resistant populations for future resistance monitoring programs. Highlights: Susceptibility to spinosad investigated in Rhyzopertha dominica. Susceptibility in wheat varied little between 18 Australian field populations. Discriminating dose of 1 mg kg −1 (1 ppm) recommended for resistance monitoring.